Molecular expression, characterization and mechanism of ALAS2 gain-of-function mutants - Vassili Tchaikovskii; Robert J. Desnick; David F. Bishop (BMC, 2019)
Abstract Background X-linked protoporphyria (XLP) (MIM 300752) is an erythropoietic porphyria due to gain-of-function mutations in the last exon (Ducamp et al., Hum Mol Genet 22:1280-88, 2013) of the erythroid-specific aminolevulinate synthase gene (ALAS2). Five ALAS2 exon 11 variants identified by the NHBLI Exome sequencing project (p.R559H, p.E565D, p.R572C, p.S573F and p.Y586F) were expressed, purified and characterized in order to assess their possible contribution to XLP. To further characterize the XLP gain-of-function region, five novel ALAS2 truncation mutations (p.P561X, p.V562X, p.H563X, p.E569X and p.F575X) were also expressed and studied. Methods Site-directed mutagenesis was used to generate ALAS2 mutant clones and all were prokaryotically expressed, purified to near homogeneity and characterized by protein and enzyme kinetic assays. Standard deviations were calculated for 3 or more assay replicates. Results The five ALAS2 single nucleotide variants had from 1.3- to 1.9-fold increases in succinyl-CoA Vmax and 2- to 3-fold increases in thermostability suggesting that most could be gain-of-function modifiers of porphyria instead of causes. One SNP (p.R559H) had markedly low purification yield indicating enzyme instability as the likely cause for XLSA in an elderly patient with x-linked sideroblastic anemia. The five novel ALAS2 truncation mutations had increased Vmax values for both succinyl-CoA and glycine substrates (1.4 to 5.6-fold over wild-type), while the Kms for both substrates were only modestly changed. Of interest, the thermostabilities of the truncated ALAS2 mutants were significantly lower than wild-type, with an inverse relationship to Vmax fold-increase. Conclusions Patients with porphyrias should always be assessed for the presence of the ALAS2 gain-of-function modifier variants identified here. A key region of the ALAS2 carboxyterminal region is identified by the truncation mutations studied here and the correlation of increased thermolability with activity suggests that increased molecular flexibility/active site openness is the mechanism of enhanced function of mutations in this region providing further insights into the role of the carboxyl-terminal region of ALAS2 in the regulation of erythroid heme synthesis.